VALUE-BASED ATTITUDE TOWARDS CHILDREN IN S. V. KONDRATYEVA'S CONCEPTAS A PSYCHOLOGICAL RESOURCE FOR PARENTAL RESILIENCE (Universal International Scientific Journal, 2026)
This article examines the value-based attitude toward children as a significant psychological factor in parental resilience. Based on empirical research, the structural components of parental value-based attitudes (cognitive, emotionally motivated, and behavioral) are analyzed and their relationship with indicators of resilience, purpose in life, and self-efficacy. The study involved parents of elementary school students, and standardized psychometric methods and statistical analysis were used for assessment. The results confirm that emotional acceptance of the child and meaningful parental roles contribute to increased stress resilience and psychological stability in parents. The study findings can be used in family psychological support practices and in the development of parenting support programs.
Keywords: value attitude towards children; parental resilience; parenting; emotional acceptance; life-purpose orientations; self-efficacy.